FDTD and transfer matrix methods for evaluating the performance of photonic crystal based microcavities for exciton-polaritons. (14th October 2016) - Liu, Yi-Cheng; Byrnes, Tim
Abstract: We investigate alternative microcavity structures for exciton-polaritons consisting of photonic crystals instead of distributed Bragg reflectors. Finite-difference time-domain simulations and scattering transfer matrix methods are used to evaluate the cavity performance. The results are compared with conventional distributed Bragg reflectors. We find that in terms of the photon lifetime, the photonic crystal based microcavities are competitive, with typical lifetimes in the region of ∼20 ps being achieved. The photonic crystal microcavities have the advantage that they are compact and are frequency adjustable, showing that they are viable to investigate exciton-polariton condensation physics.